2012
DOI: 10.1097/aci.0b013e32835090c9
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial stress and asthma morbidity

Abstract: Purpose of review The objective of this review is to provide an overview and discussion of recent epidemiologic and mechanistic studies of stress in relation to asthma incidence and morbidity. Recent findings Recent findings suggest that stress, whether at the individual- (i.e., epigenetics, perceived stress), family- (i.e., prenatal maternal stress, early life exposure or intimate partner violence) or community- (i.e.., neighborhood violence; neighborhood disadvantage) level influences asthma and asthma mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
77
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(87 citation statements)
references
References 42 publications
7
77
0
3
Order By: Relevance
“…9 Research consistently suggests a complex interplay between individual (e.g., genetic predisposition), family (e.g., parental smoking, socioeconomic status, and maternal stress), and environmental risk factors (e.g., allergen exposure), which undermine asthma management and exacerbate vulnerability to poor outcomes. [10][11][12][13][14][15][16] Community violence, which may range from perceived threats to direct victimization, is one stressor that has an especially robust connection to asthma morbidity, as it is proposed to precipitate asthma exacerbations and result in increased healthcare utilization. 17,18 In a prospective study, adults with asthma who were exposed to violence had 92 times more asthma-related ED visits and 92 times more hospitalizations compared with adults without community violence exposure.…”
Section: Introductionmentioning
confidence: 99%
“…9 Research consistently suggests a complex interplay between individual (e.g., genetic predisposition), family (e.g., parental smoking, socioeconomic status, and maternal stress), and environmental risk factors (e.g., allergen exposure), which undermine asthma management and exacerbate vulnerability to poor outcomes. [10][11][12][13][14][15][16] Community violence, which may range from perceived threats to direct victimization, is one stressor that has an especially robust connection to asthma morbidity, as it is proposed to precipitate asthma exacerbations and result in increased healthcare utilization. 17,18 In a prospective study, adults with asthma who were exposed to violence had 92 times more asthma-related ED visits and 92 times more hospitalizations compared with adults without community violence exposure.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Puerto Ricans were more likely to report symptoms of post-traumatic stress disorder (PTSD) or to have a perievent panic attack after the attacks of September 11, 2001 than members of other ethnic groups (9). PTSD and psychosocial stress have been associated with increased asthma morbidity (11), and we previously showed that physical or sexual abuse (a traumatic event) is associated with increased asthma morbidity in Puerto Rican children of school age living in San Juan, Puerto Rico (4). The biologic mechanisms linking exposure to violence or psychosocial stress and asthma are largely unknown (11).…”
mentioning
confidence: 99%
“…PTSD and psychosocial stress have been associated with increased asthma morbidity (11), and we previously showed that physical or sexual abuse (a traumatic event) is associated with increased asthma morbidity in Puerto Rican children of school age living in San Juan, Puerto Rico (4). The biologic mechanisms linking exposure to violence or psychosocial stress and asthma are largely unknown (11).…”
mentioning
confidence: 99%
“…In recent years, several studies have provided valuable insights into the relationship between psychosocial factors and asthma morbidity [150]. HAVLAND et al [151] investigated the association between maternal anxiety and offspring asthma in a ''children of twin''-design study.…”
Section: Studies In Twinsmentioning
confidence: 99%